Penyuluhan Edukasi Urgensi Penyakit Sistemik dan Pemeriksaan Kolesterol Pada Usia Produktif di Warga Lingkunga KM 14 Kota Palembang - Aprida Manurung; Novita Anggraini; Margareta Haiti; Mustika Sari Hutabarat; Lidwina Septie Ch; Agnes Felicia Lubis (Compromise Journal Community Proffesional Service Journal, 2023)
Routine health checkups are simple and easy to do. Health checks can include physical examinations, laboratory tests, and followed by consultations. The purpose of this service activity is to be able to provide counseling to residents regarding the prevention of non-communicable diseases (PTM) and conduct examinations such as blood pressure checks and cholesterol checks. The purpose of these tests is to detect previously unknown diseases or health problems. This way, you can improve your health early on, before the condition gets worse. There are many health problems that can be detected through regular health checks. These diseases are the main diseases that are commonly suffered by citizens, especially in Indonesia. Residents of KM 14 neighborhood in Palembang City mostly consist of working age residents, who have more opportunities to work and have less time to undergo health checks and when residents are on vacation, health services are also closed. Most of the residents of KM 14 Palembang City do not know the importance of health checks and do not have the right time to visit health services. So the PKM team began to offer solutions by conducting physical examinations and education about systemic diseases such as high blood pressure, gout, and diabetes.